Molecular, immunological, and histological study of Cryptosporidium parvum in local duck Anas platyrhnchos in some regions of Mosul city, Iraq - Nawras T. Al-Hassan; Alyaa A. Al-Safo (Iraqi Journal of Veterinary Sciences, 2024)
The species and strain of Cryptosporidium parvum genotype in domestic ducks were recorded for the first-time using sequencing technologies in this study. In addition, it looks at the spread of Cryptosporidium parvum and the methods used to diagnose it in different districts of Mosul. Ninety-one duck feces were gathered from six different districts of the city: Shallalat, Bashiqa, Ali Rash, Bartella, Al-Hamdaniya, Telkaif, Felfil, and Al-Qosh. The positive result rate was 27% (25 of the original 91), with monthly variations based on geographic region and age. The statistical analysis revealed considerable disparities in scientific procedures between the northern and eastern Mosul regions. The age factor revealed a substantial difference between 9 and 12 months. Histopathological changes in the trachea and intestinal tract were recorded. The type and strain of Cryptosporidium parvum were recorded and compared to sequences stored in the NCBI's GenBank database. The parasite's genetic invasion, was discovered to match the strains reported in China. The study concluded that for the first time in Mosul, the strain and type of Cryptosporidium parvum isolate were recorded in local ducks, with a higher incidence among local ducks aged 6-12 months than at other ages. Furthermore, its incidence was higher in the city's northern areas than in its eastern areas. Duck trachea and intestines are affected by this strain's histopathological alterations.